PROPORSI PENGELUARAN PETANI PADI SAWAH DI DESA MOPUYA KECAMATAN DUMOGA UTARA KABUPATEN BOLAANG MONGONDOW - Antonius D. Prawira; Ventje V. Rantung; Mex L. Sondakh; Lyndon R.J. Pangemanan (Universitas Sam Ratulangi, 2015)
ABSTRACTAntonius Dedy Prawira. The proportion of paddy farmers expenditure of the Mopuya Village, North Dumoga sub District, Bolaang Mongondow Regency. Under guidance of Ventje V Rantung as a chairman; Mex L Sondkh and Lyndon R.J. Pangemanan as members.The objective of this research is analyze income and expenditure, measures the proportion of the paddy farmers expenditure and to by classifying large paddyfarmers have more than 5 ha moderate paddy farmers who have from 3,01 ha to 5 ha and small paddy farmers who have less than 3 ha in Mopuya Village, North Dumoga District Bolaang Mongondow RegencyThe study lasted for 3 months from preparation to writing in to Mopuya Village North Dumoga District Bolaang Mongondow Regency august of reports than in june to august 2014, North Sulawesi Province. The data taken were primary data obtained by direct intervews with owners of paddy farmers, using a list of questions that have been prepared secondary data obtained from the office of the Village and rice milling. Sampling was done with less farmers by using cluster random sampling method (sampling in group), by dividing the farmer to farmer groups with board ownersip of the wetland; farmers who have small paddy fields (< 3 ha), farmer who have moderate paddy fields (3,01 to 5 ha) and farmers who have large paddy fields (> 5 ha), each group of 10 farmers. Total number of respondents as a sample of 30 farmers.The research result indicated that income for small farmers were USD 1,567,875 to USD 6,024,500 million, while for the moderate farmers were USD 7,095,000 million to USD 10,906,500 million and for large farmers were USD 10,620,500 million to USD 15,434,000 million. The greater area of land cultivated, the smaller the proportion of expenditure on food, while for non-food expenditure increases.